Subcronic Toxicity and Hepatoprotector Potential of Miana Leaf Extract on White Rat Which Indicated by Anti Tuberculosis Drugs (Indian Journal of Forensic Medicine & Toxicology, 2020)
Damage to liver function is the most common cause of patients or doctors stopping treatment. Antituberculosis (OAT) drug-induced hepatotoxicity is mainly caused by oxidative stress caused by drugs andmetabolites. Subchronic toxicity is one of the conditions for testing long-term used drugs such as OAT.The research aims to determine the potential of miana leaf extract (EDM) as a hepatoprotector and preventtoxicity due to OAT administration. The study used 5 groups of Wistar rat test animals namely K1 (normalmice given placebo); K2 (OAT-induced mice given placebo); K3 (OAT-induced mice given MakassarEDM); K4 (OAT-induced mice given EDM Kupang); K5 (OAT-induced mice given Silymarin). Tests onmice were carried out after 30 days of treatment with parameters SGOT, SGPT, total bilirubin, creatinineand liver histopathology. The results showed that EDM has the potential as a hepatoprotector by preventingan increase in SGOT, SGPT and total bilirubin so as to avoid liver damage due to OAT induction. EDM hasthe potential to prevent toxicity due to the administration of OAT with creatinine parameters.
Keywords: miana leaf extract, OAT, hepatoprotector, toxicity